Safety and effectiveness of atorvastatin and rosuvastatin monotherapy and with fibrate combination among patients receiving protease inhibitors - อังคศรีทองกุล, สมคิด (Disease Control Journal, 2014)
This study aimed to determine the safety and the effectiveness of atorvastatin and rosuvastatin using alone compared with atorvastatin and rosuvastatin using with fibrate (gemfibrozil or fenofibrate) in reducing low-density lipoprotein cholesterol (LDL-C), and achieving LDL-C goal according to NCEP ATPIII guideline among HIV-infected patients who were recieving boosted-Pls or Pls. A retrospective cohort study was conducted by using medical records among patients who came for follow up during January 1, 2010 through June 30, 2012 at Bamrasnaradura Infectious Disease Institute. The participants must age >18 years at statin-starting date, had LDL-C records at least 2 times: within 3 months before the first statin was used with boosted Pls (or PI) and after being used concomitantly for at least 3 months and had never used any statin 3 months before boosted-Pls starting. Lipid profiles and related data at least for 1 year before and after statins/boosted Pls using were determined and collected. Outcomes were the rates of adverse events (AEs) and the effectiveness of atorvastatin and rosuvastatin: mean % LDL-C reduction and LDL-C goal achievement according to NCEP ATP III. Of 116 patients, 82 were men and 34 were women: mean of age was 45 years; 53 used atorvastatin: 14 with gemfibrozil and 14 with fenofibrate; 63 used rosuvastatin: 14 with gemfibrozil and 15 with fenofibrate. AEs were found 4 (3.596), 2 with myalgia and discontinued statins and another 2 with CPK- increasing >2 times of ULN but they could continue both statins and fibrates. Of 4 AEs cases, 3 used LPV/r regimen and 1 used LPV/ATV/r, all used rosuvastatin 10 mg daily with fibrates: 3 with gemfibrozil and 1 with fenofibrate. Of total, rosuvastatin was more effective than atorvastatin, both mean % LDL-C reduction (33.096 vs 24.196, p = 0.015) and LDL-C goal achievement (68.396 vs 49.196; OR = 2.23, p = 0.036). This study revealed that statin-monotherapy comparing with statin- fibrate combination didn’t affect the effectiveness of both rosuvastatin and atorvastatin in reducing LDL-C levels (p = 0.395 and 0.619, respectively) and in achieving the goal of LDL-C (p = 0.314 and 0.185 respectively). Of 59 cases who used statins alone, rosuvastatin was more effective than atorvastatin in reducing LDL-C (34.996 vs 22.996, p = 0.025) and achieving LDL-C goal (OR = 4.27, p = 0.008). Of 57 cases who used statins with gemfibrozil or fenofibrate, the mean 96 LDL-C reduction in rosuvastatin group and atorvastatin group did not significantly differ (p = 0.778 and 0.235, respectively), as well as achieving the goal did not significantly differ too (OR = 2.75, p = 0.225 and OR = 0.64, p = 0.550, respectively). In summary, if it's necessary to use atorvastatin or rosuvastatin with gemfibrozil or fenofibrate, atorvastatin is preferable to rosuvastatin for more safety and no difference in effectiveness.